2019
DOI: 10.1088/1755-1315/260/1/012108
|View full text |Cite
|
Sign up to set email alerts
|

Biology and growth of Asiatic Hard Clam (Meretrix meretrix) population in Tanjung Balai, North Sumatera

Abstract: Asiatic hard clam (Meretrix meretrix) was one of molluscs (bivalve) with economical value. However, fishing activities were presumed to cause a decline in population. This condition was strengthened by the size of the clam which became smaller nowadays. The purpose of this study was to determine spatial distribution of M. meretrix, length distribution, and length-weight relationship. The study was conducted at 3 stations, consisted of Station I at Asahan River estuary which was located by mangrove forest, Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…This study is the first of its kind to investigate the diversity of invertebrate prey in the diet of catfish using DNA barcodes. The economically important clams (Meritxix meritrix ) (Yeh et al, 2016;Desrita et al, 2019) and mussel (Perna viridis) (Sulvina et al, 2020) found in the diet of A. maculatus in this study is of concern, as local populations were known to depend on these resources for food. Since accurate identification of macro-benthic invertebrates from benthophagous fish could facilitate the assessment of human impact on the ecosystem (Tupinambás et al, 2015), further studies could be directed toward a detailed picture of trophic levels in DNA barcoding based gut analysis of other catfish and fin fish species inhabiting Vellar estuary (Khan et al, 2011;Sakthivel et al, 2012).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…This study is the first of its kind to investigate the diversity of invertebrate prey in the diet of catfish using DNA barcodes. The economically important clams (Meritxix meritrix ) (Yeh et al, 2016;Desrita et al, 2019) and mussel (Perna viridis) (Sulvina et al, 2020) found in the diet of A. maculatus in this study is of concern, as local populations were known to depend on these resources for food. Since accurate identification of macro-benthic invertebrates from benthophagous fish could facilitate the assessment of human impact on the ecosystem (Tupinambás et al, 2015), further studies could be directed toward a detailed picture of trophic levels in DNA barcoding based gut analysis of other catfish and fin fish species inhabiting Vellar estuary (Khan et al, 2011;Sakthivel et al, 2012).…”
Section: Discussionmentioning
confidence: 90%
“…Previous nationalised efforts to barcoding the marine diversity (Lakra et al, 2010;Bineesh et al, 2014;Bamaniya et al, 2015) along with localised efforts to barcode the diversity of Vellar estuary (Khan et al, 2010(Khan et al, , 2011PrasannaKumar et al, 2012;Thirumaraiselvi et al, 2015;Rajthilak et al, 2015;Rahman et al, 2013Rahman et al, , 2019Hemalatha et al, 2016;Sahu et al, 2016;Palanisamy et al, 2020;Manikantan et al, 2020;Thangaraj et al, 2020;Narra et al, 2020) resulted in strengthening the reference library which insured that no ambiguous sequences were present in this study (as all sequences were identified to species level). Identification success was likely due to the use of previously generated references sequences from Indian waters from morphologically verified species and published through reference databases (such as GenBank and BOLD).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outer shell is white, with a purplish tinge on the postero-dorsal slope. Typically found in the sand and mud of intertidal areas and adapted to less saline environments, it feeds on plankton and detritus [42]. posterior edges.…”
Section: Mollusca-bivalviamentioning
confidence: 99%
“…Typically found in the sand and mud of intertidal areas and adapted to less saline environments, it feeds on plankton and detritus [42].…”
Section: Mollusca-bivalviamentioning
confidence: 99%